2022
DOI: 10.3390/ijerph19042252
|View full text |Cite
|
Sign up to set email alerts
|

In the Eye of the Storm: A Quantitative and Qualitative Account of the Impact of the COVID-19 Pandemic on Dutch Home Healthcare

Abstract: The COVID-19 pandemic has severely affected healthcare delivery across the world. However, little is known about COVID-19’s impact on home healthcare (HHC) services. Our study aimed to: (1) describe the changes in volume and intensity of HHC services and the crisis management policies implemented; (2) understand the responses and the experiences of HHC staff and clients. We conducted an explanatory sequential mixed methods study. First, retrospective client data (N = 43,495) from four Dutch HHC organizations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 20 publications
0
18
1
Order By: Relevance
“…Unmet home care needs were exacerbated by the response to COVID-19 when home care services were restricted or reduced, particularly during the early phase of the pandemic. Personal care and therapies for persons with dementia were significantly interrupted, although, home care services rebounded to historical highs [ 8 , 34 ]. Consistent with the literature [ 35 37 ], limits on home care service and family availability were associated with LTC placement.…”
Section: Discussionmentioning
confidence: 99%
“…Unmet home care needs were exacerbated by the response to COVID-19 when home care services were restricted or reduced, particularly during the early phase of the pandemic. Personal care and therapies for persons with dementia were significantly interrupted, although, home care services rebounded to historical highs [ 8 , 34 ]. Consistent with the literature [ 35 37 ], limits on home care service and family availability were associated with LTC placement.…”
Section: Discussionmentioning
confidence: 99%
“…Through the gerontological nursing perspective, this study focused on pandemic as climatic stressor that bears high risk for both caregivers and their clients. During the first waves of COVID‐19, many formal caregivers felt they were left alone in an unsafe environment, with limited access to information and resources and with many dilemmas regarding safety precautions (Osakwe et al, 2021 ; van den Bulck et al, 2022 ). Such a state of mind might result in higher anxiety and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, formal caregivers who had to travel by public transportation from one home to another and work closely with more severely impaired older people were at greater risk to infect them or to be infected themselves. In some countries, homecare delivery to non‐urgent cases was scaled back or cancelled (van den Bulck et al, 2022 ). Due to their position in emergency work, Israeli formal caregivers provided home care even during government enforced lockdowns.…”
Section: Introductionmentioning
confidence: 99%
“…In previous literature, organizational factors have been identified as substantially driving adherence to infection prevention and control measures (Adams et al, 2021;Barratt et al, 2020;Chughtai et al, 2020;Nichol et al, 2013;Shigayeva et al, 2007); however, they were not found to be significant predictors of FPE adherence in this study. Despite challenges related to global FPE shortages experienced throughout the health care sector (Shang et al, 2020;van den Bulck et al, 2022), the proportion of respondents who reported that their needs were well met at an organizational level was very high -FPE was available and conveniently accessible, the vast majority of staff reported receiving adequate training, and media attention regarding COVID-19 was high. While there was some diversity in perceptions of organizational support and communication related to health and safety, approximately two thirds of respondents in both the adherent and non-adherent groups reported high levels of support and communication.…”
Section: Organizational Factors Influencing Adherencementioning
confidence: 99%
“…This sector, like others in global health care systems, faced extreme challenges early in the pandemic related to securing adequate supplies of facial protective equipment (FPE) and other necessary infection prevention and control (IPAC) supplies. These shortages were managed through extraordinary measures including rationing, extended use and limited reuse of these scarce resources (Shang et al, 2020;van den Bulck et al, 2022).…”
Section: Introductionmentioning
confidence: 99%